A QULITATIVE STUDY OF E-WALLET AND THE RELATION WITH CONSUMER BEHAVIOUR - Tompodung, Victory P.; Tulung, Joy E.; Pandowo, Merinda H. C. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The explanations regarding the digital wallet and its function eventually give impact toward the consumer behavior of its users; it can happen because of the different types of advantages and functions of digital wallet which varied compare to other types of payments and transactions as well. The consumer behavior tends to focus more on how the consumer behaves toward a certain thing; in this case, it regarding the behavior of the E-wallet users. The purpose of this study is to find out regarding E-Wallet and the relation with consumer behavior. This study uses a qualitative method and interviews with informants were conducted in order to gain information regarding the phenomenon. The findings of this study show that consumer behavior which constructed by 3 aspects of psychological, personal and social can be affected by the usage of E-wallet. From the results; the company can utilize on this momentum in order to gain more users and eventually profit for the company. Improvement of their current technology such as reducing the numbers of errors, a safety net for transactions and also transparency for the users of E-wallet can be ways for the company to improve. Â Keywords: e-wallet, consumer behavior, psychological, personal, sosial